Successful radical resection of pancreatic head carcinoma in a patient with replaced right hepatic artery originating from posterior inferior pancreaticoduodenal artery: a case report - Yusuke Sakamoto; Takahisa Fujikawa; Akira Tanaka (Surgical Case Reports)
Abstract Anatomical variations of hepatic arteries may be problematic in pancreaticoduodenectomy (PD). We experienced pancreatic head cancer in a patient with rare variation of hepatic artery and performed PD successfully with the resection of this artery. A 75-year-old woman showed pancreatic head tumor on CT. Preoperative CT detected rare variation of hepatic artery; posterior segmental branch of right hepatic artery (RHA-PB) originating from posterior inferior pancreaticoduodenal artery. The image also demonstrated that there was a junction between RHA-PB and anterior branch of right hepatic artery (RHA-AB). We performed PD for suspected pancreatic head cancer. We divided RHA-PB for complete resection of cancer because we preoperatively knew that there was the junction between RHA-PB and RHA-AB. She was discharged uneventfully, and there was no evidence of local recurrence throughout the whole course. Careful preoperative assessment of hepatic blood supply is the key to perform successful PD even in this troublesome situation.